Reduction in school individualized education program (IEP) services during the COVID-19 pandemic - Chen, Belinda; Rasmussen, Patrick; Legg, Mallory; Alexander, Nicole; Vedmurthy, Pooja; Asiedu, Akua; Bay, Mihee; Belcher, Harolyn; Burton, Vera Joanna; Conlon, Charles; Fine, Amena; Gill, Ryan; et al. (Frontiers in Rehabilitation Sciences, 2022)
The COVID-19 pandemic created novel challenges for school systems and students, particularly students with disabilities. In the shift to remote/distance learning, many children with disabilities did not receive the special education and related services defined in their individualized education program (IEP). Patients attending an outpatient tertiary care center for neurodevelopmental disabilities in Maryland were surveyed on the impact of the pandemic on medical and educational services provision and access. Nearly half (46%) of respondents qualified for special education and related services through an IEP before the start of the COVID-19 pandemic. Among those with IEPs, 48% attested to reduced frequency and/or duration of special education and/or related services during the pandemic. The reduction was greatest in occupational therapy services (47%), followed physical therapy services (46%), and special education services (34%). Given the reduction in IEP services experienced by the patients, we sought education for clinicians on the rights of students with disabilities in anticipation of students’ re-entry to the classroom. A special education law attorney provided an instructional session on compensatory education and recovery services to prepare clinicians to properly inform parents about their rights and advocate for patients with unmet IEP services during the pandemic.